2016
DOI: 10.1016/j.mrgentox.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

The mutagenic assessment of an electronic-cigarette and reference cigarette smoke using the Ames assay in strains TA98 and TA100

Abstract: Salmonella typhimurium strains TA98 and TA100 were used to assess the mutagenic potential of the aerosol from a commercially available, rechargeable, closed system electronic-cigarette. Results obtained were compared to those for the mainstream smoke from a Kentucky reference (3R4F) cigarette. Two different test matrices were assessed. Aerosol generated from the e-cigarette was trapped on a Cambridge filter pad, eluted in DMSO and compared to cigarette smoke total particulate matter (TPM), which was generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 26 publications
4
44
1
Order By: Relevance
“…Moreover, oxidative DNA lesions have been proposed to cause the vast majority of human mutations [79]. Our data is in apparent contradiction with the fact that ECs have been deemed non-mutagenic to Ames Salmonella tester strains TA98 and TA100 [80, 81]. However, none of the previous studies included the strains TA102 or TA104 which have the highest sensitivity for the detection of mutagenesis induced by oxidative or cross-linking agents [82].…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Moreover, oxidative DNA lesions have been proposed to cause the vast majority of human mutations [79]. Our data is in apparent contradiction with the fact that ECs have been deemed non-mutagenic to Ames Salmonella tester strains TA98 and TA100 [80, 81]. However, none of the previous studies included the strains TA102 or TA104 which have the highest sensitivity for the detection of mutagenesis induced by oxidative or cross-linking agents [82].…”
Section: Discussioncontrasting
confidence: 68%
“…TA104 has also been reported to be particularly sensitive to carbonyl based compounds [83], as those reported to be present in EC aerosol. Moreover, the Organization for Economic Co-operation and Development (OECD) recommends testing a battery of at least five tester strains to capture the full range of chemical interactions and mutagenic events acting via different modes of action[81]. Another variable to consider, is the fact that toxicant yield varies with EC brand, product model, e-liquid flavor, e-liquid solvent, and device power [19, 21, 23, 84, 85] so it is not possible to directly compare our study to others using different ECs or e-liquids.…”
Section: Discussionmentioning
confidence: 99%
“…[64] have recently reported that e-cig aerosol is not mutagenic in the Ames assay in bacterial strains TA98 and TA100. The limited mutagenicity of e-cig vapor found in this in vitro study as well as in those reports [65, 66] may imply that e-cig is worthy of further consideration as a putatively modified-risk tobacco substitute. The view that e-cig may pose a reduced risk as compared to combustible cigarettes is consistent with the lower concentrations of most toxicants and carcinogens in e-cig vapor than cigarette smoke [813].…”
Section: Discussionsupporting
confidence: 54%
“…Existing studies suggest that the toxicological responses are qualitatively similar to smoking, e.g., exposing cell lines and cultures to the aerosols induces a pro-inflammatory effect (185, 186), disruption to epithelia barriers (187), oxidative stress (188), cytotoxicity (189), neutrophil inflammatory response (190) and DNA damage (191, 192). However, the magnitude of effect is low compared to cigarette smoke and aerosols were not found to be mutagenic (193). Normal human bronchial epithelial (NHBE) cells exposed to e-cig aerosols, with or without nicotine, increase IL-6 and IL-8 cytokine levels (194).…”
Section: Introductionmentioning
confidence: 99%